Teacher Assistance in using Educational Game-Based Tools Six Aspects of Child Development in Salsa Kindergarten the Village of the Cinta Rakyat, District Percut Sei Tuan, Deli Serdang - Virganta, Anada Leo; Kamtini, Kamtini; Novitri, Dwi Maya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Quality education requires teachers who understand the needs of early childhood to achieve a level of developmental achievement that is appropriate for their age. Besides qualified teachers, interesting learning is also needed for children through objects that are concretely present in the midst of children. The purpose of this service is to provide guidance and assistance for PAUD teachers in the use of educational game tools appropriate to stimulate six aspects of child development in Salsa Kindergarten in Percut Sei Tuan District. The educational game tool used is called Magic BABO (Block Book). In particular, the purpose of this service is divided into two forms (1) the use of the Magic BABO educational game tool (2) Assessment of early childhood development. The method of implementing service activities is carried out gradually and continuously and comprehensively through continuous mentoring activities and simulations of Magic BABO educational game tools based on six aspects of early childhood development. The results of this mentoring are moral in the form of increasing teacher skills in using Magic BABO educational tools, increasing teacher knowledge in preparing assessments based on six aspects of child development, physical results are the existence of Magic BABO educational tools based on six aspects of early childhood development that can be used by the teacher in the implementation of learning.